Sebaran akuifer dan pola aliran air tanah di Kecamatan Batuceper dan Kecamatan Benda Kota Tangerang, Propinsi Banten - Mohamad Sapari Hadian; Undang Mardiana; Oman Abdurahman; Munib Ikhwatun Iman (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no3.20061Geologically the Batuceper and Benda Sub-Regencies belongs to the western part of the Jakarta Basin. The area is covered by coastal alluvial and delta deposits, and volcanic product. Understanding the distribution and groundwater pattern, either in the shallow part or the deep part, are of the basic thing for a geometric model and its groundwater fl ow in identifying the groundwater conservation. The result of the aquifer distribution, either in the shallow or the depth parts, was approached by the geoelectrical and hydrogeological surveys in the fi eld and well data that has resulted in aquifer distribution, either in the shallow or the deep parts. In general, the shallow aquifer developed downward becomes semi confi ned and confi ned aquifers. Groundwater fl ow pattern indicated local cones depression of groundwater level, especially around the city. Depression of groundwater level is considered to be related to the natural shape of aquifer as lences. However, it was possible to be caused by over pumping in this zone.